Litter traits for gilts fed 4 or 7.4 lb feed during the first ten days after breeding - Duane L Davis; Z Zhang; Jeffrey S Stevenson (Kansas Agricultural Experiment Station Research Reports, 1988)
We tested the effects of feeding 4 or 7.4 lb of a complete gestation diet to gilts during days 0 to 2 or 3 to 10 after first detected estrus (day 0) and mating. There was a tendency (P = .11) for the 7.4 lb/day treatment to increase litter size when fed from day 0 to 2 and to decrease (P = .17) litter size when fed from day 3 to 10. Gilts artificially inseminated at puberty farrowed fewer (P<.05) pigs than gilts inseminated at a second or later estrus.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Feeding level; Flushing; Embryo survival; Litter traits; Fertility